Effect on indigenous die spacer thickness at varied evaporation times - V Shweta; Shalini Joshi; Chandrashekar Sajjan; Priyanka Konin; Aayesha Razzaque; Sangamma K Tippashetty (Wolters Kluwer Medknow Publications, 2018)
Aim: The present study was conducted to compare the effect of evaporation at different time intervals on film thickness at various applications of indigenous die spacer (S) Surana Enterprises, Mangalore Dental Corporation, India and TRUFIT GEO. TAUB PROD. & FUSION CO. INC. Jersey City, N.J Die spacer on ultrarock KALABHAI, Karsan, India die stone (DI) and Resin modified gypsum SynaRock XR, DFS GmbH, Germany die stone (DII). Materials and Methods: A total of 200 samples were prepared for study, and each sample was used for specific number of die spacer application (1, 2, 3, 4, or 5) after its evaporation at specific interval of time (0 h, 2 h, 4 h, 8 h, or 24 h). The specimens so obtained were then sectioned and die spacer thickness was measured using a stereo microscope. One-way analysis of variance was used for study parameters with 5% level of significance followed by Tukey's HSD post hoc test. Results: The highest mean value of die spacer thickness of 32.85 ± 0.28 μm was for SynaRrock die stone sample with 5 applications of TRU-FIT die spacer after 24 hours of evaporation and least of 13.80 ± 0.02 μm for ultrarock die stone sample with 1 application of Surana die spacer after 0 hour of evapouration. There is a significant difference in all subgroups at various evaporation time intervals. Conclusions: Evaporation of volatile substances at various time intervals varies the thickness of die spacer and thus affects the casting relief. The indigenous die spacer and die stone can also be used effectively.